Spinal Cord Stimulation for Refractory Angina Pectoris: Current Status and Future Perspectives, a Narrative Review - Roberto Gazzeri; Jacopo Mosca; Felice Occhigrossi; Marco Mercieri; Marcelo Galarza; Matteo Luigi Giuseppe Leoni (Journal of Cardiovascular Development and Disease)
Refractory angina pectoris (RAP) is a clinical syndrome characterized by persistent chest pain caused by myocardial ischemia that is unresponsive to optimal pharmacological therapy and revascularization procedures. Spinal cord stimulation (SCS) has emerged as a promising therapeutic option for managing RAP, offering significant symptom relief and improved quality of life. A systematic literature review was conducted to evaluate the clinical effectiveness, mechanisms of action, and safety profile of SCS in treating RAP. Comprehensive searches were performed in PubMed, Scopus, and Web of Science for studies published between 1990 and 2023. Of 328 articles identified, 6 met the inclusion and exclusion criteria for final analysis. The included studies consistently demonstrated that SCS significantly reduces the frequency of anginal episodes and nitroglycerin use while improving exercise capacity and quality of life. Proposed mechanisms include modulation of pain signals via the gate control theory, enhancement of autonomic balance, and redistribution of myocardial perfusion. Novel stimulation modalities, including high-frequency, Burst, and Differential Target Multiplexed (DTM), show potential advantages in enhancing patient comfort and clinical outcomes. Nevertheless, long-term studies are necessary to validate these findings and establish the comparative efficacy of these advanced technologies. SCS is a safe and effective therapy for patients with RAP who are unsuitable for surgical interventions. Innovations in neurostimulation, including closed-loop systems and personalized treatment strategies have the potential to further optimize outcomes. Rigorous clinical trials are needed to consolidate the role of SCS as a cornerstone therapy for the management of RAP.